2007
DOI: 10.1007/s10654-007-9188-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexually transmitted infections in HIV-1 infected pregnant women in Europe

Abstract: We investigated prevalence of sexually transmitted infections (STI) in a cohort of HIV-1-infected pregnant women and described factors associated with STI diagnosis, as a nested study within the European Collaborative Study (ECS). The ECS is a cohort study in which HIV-infected pregnant women are enrolled and their children followed from birth, according to standard clinical and laboratory protocols. Information on STIs diagnosed during pregnancy was collected retrospectively from the antenatal records of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…In the present study, we found that CT infection was associated with low CD4+ cell counts, and this association confirms the findings from previous Brazilian and European studies (8) (23) . In this context, patients with immunosuppression have an increased risk of infection, and their CD4+ T-cell counts and behavioral risk factors should be considered and monitored by health professionals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found that CT infection was associated with low CD4+ cell counts, and this association confirms the findings from previous Brazilian and European studies (8) (23) . In this context, patients with immunosuppression have an increased risk of infection, and their CD4+ T-cell counts and behavioral risk factors should be considered and monitored by health professionals.…”
Section: Discussionsupporting
confidence: 93%
“…However, a Canadian study reported a much lower prevalence of CT infection (0.6%) (21) . Our results regarding the prevalence of CT infection are consistent with the results from studies that were performed in Rio de Janeiro (2.2%) (22) , Europe (1%) (23) , and Africa (2.6%) (24) .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with other studies that reported similar trends in behavioral risk among other high-risk population groups. [17][18][19] HIV-infected individuals were more likely to report unprotected sex than their HIV-uninfected counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding reduction of STI incidence in women living with HIV, two studies individually mentioned favorable effects of behavioral interventions, but the results could not be pooled in a metaanalysis. STI diagnosis is a critical public health outcome in behavioral intervention trials, since solid evidence backs the biological pathways by which STI facilitate HIV transmission and the negative effects of multiple sexually transmitted infections, especially in women living with HIV 4,5,53 . We therefore emphasize that even small reductions in STI incidence could favor critical reductions in HIV morbidity and its associated treatment cost.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges directly affect their sexual practices. Women living with HIV are at increased risk for sexually transmitted infections (STI) 4,5 , cervical dysplasia, and genital cancer 6,7 . Concurrent STI and HIV also increase the risk of female-to-male HIV transmission during sexual intercourse 5 and the risk of mother-to-child HIV transmission by pregnant women.…”
Section: Introductionmentioning
confidence: 99%